Progress in Industrial Mathematics at ECMI 2008 - Fitt, Alistair D.; Norbury, John.; Ockendon, Hilary; Wilson, Eddie; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This volume is the Proceedings of the European Conference on Mathematics for Industry held in London in June 2008. The aim of the meeting was to reinforce the role of mathematics as an overarching resource for industry and business. Contributions cover a wide range of mathematical techniques and the applications include manufacturing and technology, finance and policy-making, networks, medicine, and sport.
Plenary Lectures -- Minisymposia -- Contributed Papers.
Keywords: Mathematics; Differential equations, partial; Computer science -- Mathematics; Computer science; Numerical analysis; Distribution (Probability theory).; Economics -- Statistics; Mathematics; Computational Mathematics and Numerical Analysis; Partial Differential Equations; Computational Science and Engineering; Numerical Analysis; Probability Theory and Stochastic Processes; Statistics for Business/Economics/Mathematical Finance/Insurance.